2014
DOI: 10.5430/jha.v3n4p109
|View full text |Cite
|
Sign up to set email alerts
|

Hospital readmission rates in Medicare

Abstract: Hospital readmissions are the focus of many recent efforts to improve quality and reduce spending under the Affordable Care Act (ACA). We examined variations in Medicare readmission rates by hospital characteristics (e.g., type, size, utilization) and Medicare patient mix (i.e., share of dual eligible beneficiaries, share of patients under 65 years of age, health status). Using 2010 data from 3,543 short-stay Medicare-certified hospitals, readmission rates were higher for hospitals that served a greater share … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The results of this study also show that higher occupancy rate is associated with higher readmission rates for AMI, CHF, and pneumonia. These results are similar to those of Erdem et al, 66 who found that readmission rates increased with hospitals’ occupancy rate. This increase may result from the premature discharge of patients from hospitals to free up the beds for additional patients.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study also show that higher occupancy rate is associated with higher readmission rates for AMI, CHF, and pneumonia. These results are similar to those of Erdem et al, 66 who found that readmission rates increased with hospitals’ occupancy rate. This increase may result from the premature discharge of patients from hospitals to free up the beds for additional patients.…”
Section: Discussionsupporting
confidence: 91%
“…LOS, hospital costs, or discharge destination are outcomes associated with healthcare utilization or medical service use in a broad sense and are related to a series of potential cost-saving factors for healthcare [65]. For example, a reduction of LOS can decrease inpatient hospital costs and increase hospital bed availability, increasing the overall cost-efficiency of hospitals [66].…”
Section: Discussionmentioning
confidence: 99%
“…All patients in our study had a complex social situation not suitable for ED practices. Erdem et al [31] suggests, in a study on readmission rates in medical care at a large hospital in the US, that a large hospital may serve sicker or more complex cases which makes care coordination more difficult. Since the hospital where the study was performed is the largest hospital in the area that might also be true for this hospital.…”
Section: Discussionmentioning
confidence: 99%